A First Look at Dissolved Ge Isotopes in Marine Sediments - Baronas, J. Jotautas; Hammond, Douglas E.; Rouxel, Olivier J.; Monteverde, Danielle R. (Frontiers in Earth Science, 2019)
The removal of chemical species from seawater during the precipitation of authigenic minerals is difficult to constrain but may play a major role in the global biogeochemical cycles of some elements, including silicon (Si) and germanium (Ge). Here, we present Ge/Si, δ74Ge, and supporting chemical data of pore waters and core incubations at three continental margin sites in California and the Gulf of Mexico. We used these data to partition Ge release and uptake by the various allogenic (delivered via sedimentation) and authigenic (formed in situ) phases in these sediments. About half of the pore water Ge (δ74Gepw = 1.3-2.4‰) is supplied by biogenic silica dissolution (δ74Ge ~3‰), with the other half contributed by lithogenic particulates (δ74Ge ~0.6‰). The highest Ge/Si (~ 3µmol/mol) and lowest δ74Ge (1.3-1.9‰) are observed at the Fe redox horizon, suggesting a supply from detrital Ge-rich Fe oxides. The precipitation of authigenic phases (most likely aluminosilicate clays) in deeper sediments preferentially incorporates Ge over Si, resulting in low pore water Ge/Si (~ 0.3µmol/mol). The lack of corresponding δ74Gepw trend indicates negligible Ge isotope fractionation during this process. Ge fluxes measured via core incubations were variable and appeared strongly controlled by Fe redox behavior near the sediment-water interface. In some cases, reductive Fe oxide dissolution appeared to enhance the benthic Ge flux by over 100% and released fractionated low δ74Ge of ~–0.7‰, resulting in overall benthic δ74Geinc between -0.2 and 3.6‰, depending on Fe oxide contribution to Ge flux. We estimate that detrital inputs supply 19±15% of total dissolved Ge to continental margin pore fluids globally, resulting in an average dissolved δ74Ge of 2.5±0.4‰. Assuming 10-60% of pore water Ge is captured by the authigenic aluminosilicate sink, the dissolved Ge flux to the ocean derived from terrigenous inputs should be roughly 2.4-6.4 Mmol/y, much higher than previously estimated. Our results imply that authigenic Si burial in continental margins should be in the range of 0.9-8.1Tmol/y (best estimate 3.1 Tmol/y), sufficient to close the global marine Si budget.